Lattice Boltzmann Study of a Vortex Ring Impacting Spheroidal Particles (Advances in Applied Mathematics and Mechanics, 2014)
Interaction of vortex rings with solid is an important researchtopic of hydrodynamic. In this study, a multiple-relaxation time(MRT) lattice Boltzmann method (LBM) is used to investigate the flowof a vortex ring impacting spheroidal particles. The MRT-LBM isvalidated through the cases of vortex ring impacting a flat wall.The vortex evolution due to particle size, the aspect ratio of aprolate particle, as well as Reynolds $(Re)$ number are discussed indetail. When the vortex ring impacting a stationary sphere, theprimary and secondary vortex rings wrap around each other,which is different from the situation of the vortex ringimpacting a plate. For the vortex ring impacting with a prolatespheroid, the secondary vortex ring stretches mainly along the longaxis of the ellipsoid particle. However, it is found that after thevortex wrapping stage, the primary vortex recovers along the shortaxis of the particle faster than that in the long axis,i.e., the primary vortex ring stretches mainly along the short axisof the particle. That has never been addressed in the literature.